Poklicna orientiranost študentov zdravstvene nege in zdravstvene vzgoje - Dornik, Ema (Obzornik zdravstvene nege, 2000)
The article deals with professional orientation of students of nursing care and health education at the University of Ljubljana. The empirical part deals with the question whether there are any differences among students of nursing care and health education regarding their views on professional activity. Datagathered from a survey of 118 students of health care and health educationshowed some statistically significant differences regarding general values and professional orientations. With the development of education and health care activities, also the nurses in Slovenia have the possibility od study for academic degrees.
Keywords: health care; Health education; Health occupations; poklici; Questionnaires; student; Students, nursing; študenti; zdravstvena nega; zdravstvena vzgoja; zdravstvo